A DIACHRONIC STUDY OF THE NP STRUCTURE IN GHANAIAN NEWSPAPER EDITORIALS - Afful, Isaac (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
In the last few decades, researchers have grown much interest in analyzing the structure of the NP in various domains. Dwelling on Quirk et als (1985) framework on NP complexities, this study investigates the NP structure in editorials form the Daily Graphic. Being a diachronic study, nine editorials form 1988, 1998 and 2008 were analysed. The analysis and discussion point to two key findings. First, there has been a gradual increase in the use of Head + PP structures in Ghanaian newspaper editorials. Second, the Determiner+Head has been the most preferred structure of premodification in editorials. These findings have implications for print media discourse, Historical linguistics and for further research.